2014
DOI: 10.1254/jphs.14127fp
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Inhibitory Effects of Fluvoxamine, a Selective Serotonin Reuptake Inhibitor, on Nociceptive Excitatory Synaptic Transmission in Spinal Superficial Dorsal Horn Neurons of Adult Mice

Abstract: Abstract. Fluvoxamine, a selective serotonin (5-HT) reuptake inhibitor, has been shown to exert analgesic effects in humans and laboratory animals. However, its effects on spinal nociceptive synaptic transmission have not been fully characterized. Here, whole-cell recordings were made from dorsal horn neurons in spinal slices with attached dorsal roots from adult mice, and the effects of fluvoxamine on monosynaptic A-fiber-and C-fiber-mediated excitatory postsynaptic currents (EPSCs) evoked in response to elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The finding that S2 stimulation failed to suppress ongoing discharge of WDR neurons is in line with the interpretation that the descending inhibitory action was pre-rather than postsynaptic to the studied WDR neurons, although the low level of ongoing discharge may have contributed to the failure to observe significant suppression of ongoing discharge by S2 stimulation. Nevertheless, spinally administered 5-HT 1A receptor antagonist prevented the S2 stimulation-induced prolongation of the heat-evoked response latency in the present study, and a recent patch clamp study in spinal cord slices demonstrated that serotonin suppresses nociceptive excitatory transmission from primary afferent nerve fibers due to action on presynaptic 5-HT 1A receptors (Tomoyose et al 2014). Together, these results support the proposal that presynaptic inhibition of nociceptive afferent barrage in the SDH contributed to the present findings.…”
Section: S2 Stimulation-induced Descending Antinociception: Role Of Tsupporting
confidence: 92%
“…The finding that S2 stimulation failed to suppress ongoing discharge of WDR neurons is in line with the interpretation that the descending inhibitory action was pre-rather than postsynaptic to the studied WDR neurons, although the low level of ongoing discharge may have contributed to the failure to observe significant suppression of ongoing discharge by S2 stimulation. Nevertheless, spinally administered 5-HT 1A receptor antagonist prevented the S2 stimulation-induced prolongation of the heat-evoked response latency in the present study, and a recent patch clamp study in spinal cord slices demonstrated that serotonin suppresses nociceptive excitatory transmission from primary afferent nerve fibers due to action on presynaptic 5-HT 1A receptors (Tomoyose et al 2014). Together, these results support the proposal that presynaptic inhibition of nociceptive afferent barrage in the SDH contributed to the present findings.…”
Section: S2 Stimulation-induced Descending Antinociception: Role Of Tsupporting
confidence: 92%
“…Several factors can account for reduced presynaptic neurotransmitter release, including but not limited to vesicle depletion, inactivation of release sites, and decreased presynaptic calcium influx [75]. The paired-pulse ratio (PPR) protocol measures the short term plasticity characteristics of neurons, and is a widely used approach for assessing the synaptic sites of drug action [76]. Because the PPR is inversely related to synaptic neurotransmitter release probability, our results indicate that (S)-LCM can, at least in part, decrease presynaptic glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that changes in mini frequency are a consequence of presynaptic modulations, whereas amplitude variations mainly correlate with postsynaptic modifications. As shown by several studies in various CNS areas, changes in spontaneous activity are not always paralleled by similar modifications of evoked responses; in the dorsal horn, for example, opposite effects have been observed, with an increase of spontaneous activity and a decrease of evoked responses (see, e.g., Chen & Gu, 2005;Engelman, Anderson, Daniele, & MacDermott, 2006;Tomoyose, Kodama, Ono, & Tanabe, 2014). These discrepancies could be explained in part by the different mechanisms involved in transmitter release: evoked release always depends on action potentials and calcium entry into the terminal, whereas minis are action potential independent and can occur also in the absence of extracellular calcium.…”
Section: Commentary Background Informationmentioning
confidence: 99%